Prise en compte de la singularité du contexte lors des entretiens de supervision des stages en enseignement au primaire - Hallez, Anne-Sophie; Van Nieuwenhoven, Catherine; Maes, Olivier (Canadian Journal of Education/Revue canadienne de l'éducation, 2025)
The supervision interview remains a complex moment requiring, among other things, the supervisor to consider elements of singularity that emerge from the context or the student. This contribution focuses on how the supervisor uses these elements to regulate their support and construct their evaluative judgement at the end of the interview. This study, anchored in the initial training of teachers in French-speaking Belgium, has a dual objective: on the one hand, to document the supervisor’s evaluative activity during this interview, and on the other, to support reflection, in a context of reform, on the methods of organizing, supporting, and evaluating internships. We are attempting to answer the following research questions: How does the supervisor deal with elements of singularity linked to the internship context? How do these elements of singularity contribute to the construction of evaluative adjustments in the service of the final evaluative judgement? We have opted for a single case study (Dumez, 2013 ; Merriam, 1988) based on a qualitative approach with a comprehensive and interpretative aim. The content analysis shows how an element of singularity evoked by the student during the two supervision interviews is mobilized by each supervisor to produce an adjustment in the service of the final evaluative judgment.